Vehicle Insurance Market Competitive Position Estimation in Ukraine in Terms of European Integration - Shapoval, Liudmyla; Zavora, Taina (International Journal of Engineering and Technology, 2018)
Place and importance of vehicle insurance at insurance services market in Ukraine is defined. Interaction mechanism between vehicles insurance subjects and objects is revealed. Complex estimation of domestic vehicle insurance market is carried out. Share of vehicles insurance in the structure of insurance market of Ukraine is defined. Analysis of the main indices of vehicles insurance market activity is conducted. Algorithm of Ukrainian vehicles insurance market competitive position estimation based on the method of multidimensional comparable analysis consisting of five stages is suggested. Types of vehicles insurance according to effectiveness indices are specified. Methodical grounds of Ukrainian vehicles insurance market competitive position estimation are defined. Prognostic model of vehicles insurance market competitive position is created grounded on simple linear regression which will enable modeling of vehicles insurance types condition in future according to European requirements. Â Â Â